Concentrations of Some Minerals According to Body Condition in Local Sheep: M H Al-Judi , Zainab M , Wassan,A G - Al-Judi, M H . (The Iraqi Journal of Veterinary Medicine, 2011)
Calcium, magnesium, phosphorous, sodium, potassium and chloride concentrations were estimated in 150 sheep in Baghdad classified according to body condition toemaciated, weamediu and fat sheep. Concentrations of calcium, magnesium, phosphorus, sodium, potassium and chloride in emaciated sheep were 1.88, 0.896, 1.5, 9.11, 9.04, 4.60 and 86.28 mmol/L , in weak sheep were 1.88,.876,1.34,124.11,4.89,and 95.95 mmol/L ,in medium sheep were 2.09,.986,2.10,150.57,5.25,and 105.21 ,and in fat sheep were 2.14 , 9.21, 1.93, 150.33, 4.83 and 100.63 with significant difference (P<0.05) between mineral concentrations of emaciated, weak, medium and fat sheep.